Researching the Possibilities and Attitudes Towards Expanding the Professional Competences of Radiographers in North-Eastern Bulgaria - Yordanova, Mariana Zhivkova (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2018)
The radiographer`s profession holds a significant place among the healthcare professionals in Bulgaria. Applying the medical imaging methods and techniques, performing the nuclear medicine tests and the radiotherapy procedures would be unthinkable without the participation of highly competent radiographers. The introduction of new high-tech equipment and technologies as well as of diagnosing and treating methods pose new challenges to the radiographers who now have to adopt new knowledge and skills and to perfect their competences in order to respond to the challenges of modern healthcare. This study aims at establishing the attitudes and tendency of practicing radiographers towards expanding their professional competences in their field of practice. Documentary, sociological and statistical methods have been used. Sources related to the topic have been researched. The study presents the opinion of 182 radiographers practicing in the North-Eastern region of Bulgaria regarding the attitudes and the tendency to expand the professional competences of radiographers. The interviewees have been distributed as follows: 137 radiographers (75.27%) practicing in the field of medical imaging, 42 (23.08%) – in radiotherapy and 3 (1.65%) in the field of nuclear medicine. The data has been processed mathematically and statistically and the results have been presented as graphs. The study showed that the radiographers from all three fields of practice and within the age group 22-40 years (professional experience up to 15 years) are more willing to expand their professional competences in the field of practice but after additional training compared to the age group 40-60 years (professional experience more than 15 years) who consider the competence they already possess allows them to perform the assigned tasks and that adopting new competences would increase their work load. The data obtained from the study in terms of the field of practice is quite interesting. The radiographers practicing in the field of radiotherapy are more willing to adopt new competences compared to those practicing in the field of medical imaging and nuclear medicine. This is due to some extent to the fact that radiographers working in the field of medical imaging have to deal with more work load, often in emergency situations and this would make difficult assuming new responsibilities.